A Local democracy and corruption: Economic-political relations in the corruption case of Batu City’s Mayor: - Ali Fikri Hamdhani; Ahmad Adi Susilo (Komisi Pemberantasan Korupsi, 2024)
The rise of local democracy through decentralization does not guarantee a decrease of corruption crimes in Indonesia. The good governance perspective has become common in regional governments, ignoring structural aspects and causing base-level contradictions in the localization of power. In the reformation era, reviving localized politics was an effort to reorganize the old elite forces that were influential since the New Order. This study uses the concept of localization as a new arena for the ruling elite and local entrepreneurs, who play a major role in the competition for power and wealth. This study uses a qualitative approach, analyzing Eddy Rumpoko's corruption during his two terms as Mayor of Batu City, from 2007 to 2017. Primary data is gathered through the court decision for Rumpoko's corruption crimes, while secondary data is obtained through library research in the form of books, journals, media and other related documents. The research results show that corruption in Batu City is a form of local economic-political alliance interests, especially for entrepreneurs engaged in the tourism, hotel, villa or housing and building construction industries. They have found it easier to do business since Rumpoko's time with the mobilization of bureaucrats, while he was able to maintain political power through the help of businessmen.​